Legal Security for The Board of Directors of Individual Limited Companies in The Event of Bankruptcy - Restu Adhie Charisma; M Sudirman (Siber International Journal of Advanced Law (SIJAL), 2024)
Legal Certainty for Directors of Individual Limited Liability Companies in Case of Bankruptcy, The enactment of Law Number 11 of 2020 concerning Job Creation has given birth to a new type of PT, namely a company that meets the standards of micro and small businesses, or as per Government Regulation Number 8 of 2021 concerning the Authorized Capital of Companies and Registration, Establishment, Amendments and Dissolution of Companies, it is stated that those that meet the requirements of micro and small businesses are called Individual Companies. This scientific article uses normative legal research or library legal research, namely research conducted by examining library materials or secondary data, and the type of research in this writing is normative legal research, namely it is studied with a statutory approach, meaning that a problem will be seen from its legal aspect by examining statutory regulations. The results of the study show that the Law in Indonesia still needs to be completed to form regulations regarding this individual company in separate statutory regulations outside of limited liability company law. An important conclusion from this study is that PT should ensure that the principles, regulations and essence of individual companies in the Job Creation Law do not conflict with the principles, regulations and essence of limited liability companies in the limited liability company law.